(untitled) (Dialogos, 2017)
As províncias argentinas, cada uma a seu tempo e modo, diante de mecanismos de apropriação funcional por parte do Estado Nacional, passaram a assegurar o normal desenvolvimento das relações sociais no âmbito local de produção, principalmente com o disciplinamento da força de trabalho, através da justiça, cadeia e educação. Em Córdoba, este processo se cristalizou no período entre o final da década de 1870 a meados da de 1900, com toda uma combinação de doses de coação e eliminação de alternativas para a população crioula. Mas isto não se deu isento de lutas e resistências. Como ocorreu essa passagem da “fronteira” ao “presídio”? A abordagem desta questão é a da própria constituição do trabalhador, os sujeitos da história que viriam a ser identificados com os setores populares tanto crioulos como gringos Abstract. The Argentine provinces, each one in its way and time, in front of devices of functional appropriation by the National State, had began to assure the normal development of the socials relations, on the ambit of the local production, mainly with the adoption of disciplinary measures of the work strength. Justice, prison and education fulfilled those measures. In Cordoba, such process has crystallized in the period between the final of the 1870-decade and the middles of 1900-decade, with the combination of coercion doses and the elimination of any alternative for the criolla population. Nevertheless, this didn’t happen without fight and resistance. How did this passage from the “frontier” to the “prison” happen? The focus of this issue is the constitution the workers itself, as subjects of the History, who would be identified with people’s sectors even criollos or gringos.